Reviewer on commercial law - Aquino, Timoteo B.; Sundiang, Jose R. Sr (Rex Book Store, 2025)
Insurance Code of the Philippines-- Laws on transportation and public utilities-- The Montreal Convention of 1999 and Civil aviation laws (R.A. No. 9497 and R.A. No. 6235)-- Maritime law-- Public Service Act (Commonwealth Act No. 146, as amended by R.A. No. 11659)-- Business organization-- Basic types of business organization-- Partnership-- Revised Corporation Code of the Philippines (R.A. No. 11232)-- Securities regulation Code (SRC, R.A. No. 8799) and related laws-- Philippine Competition Act (R.A. No. 10667)-- Foreign Investment Act (FIA)-- General Banking Law, Law on secrecy of deposits and related laws-- Other related laws-- Credit transactions-- Warehouse receipts law (Act No. 2137)-- Letters of credit-- Trust Receipts Law-- Bulk Sales Law-- Guaranty and suretyship-- Mortgage-- Personal Property Security Act-- Recto Law-- Financial Rehabilitation and Insolvency Act of 2010 and Concurrence and Preference of Credits-- Intellectual Property Code-- Data Privacy Act-- Negotiable Instruments Law